Delta-1 provides pleasant stem cell environs - Pelus, Louis M. (American Society of Hematology, 2014)
In this issue of Blood, Csaszar et al show that in ex vivo cultures of CD34(+) cells, simultaneous reduction of interleukin-6 receptor (IL-6R) expression on myeloid progenitor cells by Delta-1 treatment combined with removal of soluble IL-6R using a dynamically fed culture system, reduces mature myeloid cell production, leading to enhanced expansion of primitive hematopoietic stem cells.(1)